PENGEMBANGAN MEDIA PUZZLE GEOMETRI DATAR BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Aini, Zuhrotul; Maritasari, Donna Boedi; Kudsiah, Musabihatul (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
This research aims to determine the validity of puzzle media and the feasibility of mathematical puzzle media based on local wisdom in flat shape material in class IV in elementary schools and to find our student’s responses to the use of local wisdom based mathematical puzzle media in flat shape material in class IV elementary school. This research ures the ADDIE model research method which consists of five development stages, namely: analysis stage, design stage, development stage, impelementation stage and evaluation stage. The field trial was carried out in class IV of SDN 2 Korleko Selatan with 12 students as respondents. The data obtained in the research are qualitative and quantitative data. Data collection instruments include validation sheets and student response questionnaires. The results include: in media expert validation, they obtained a total score of 50, with an average score of 3.66 with good categories/criteria in the score range and 40.8 < 54, with and average score of 4.15 in the good category which is in the score range of 47, 58 58,74 in the good category. Therefore, the resulting learning media is suitable for use to obtain data in field trials. Based on the results of student responses carried out during field trials, the results of student response questionnaire on learning media had a total score of 700, indicating good students responses with an average of 47,58 X 58,7. in the good category.